Mésentente temporelle. La fabrique du patrimoine culturel urbain de Rio de Janeiro à l’épreuve des temps du territoire carioca - Véronique Zamant (Développement Durable et Territoires)
This article proposes to analyze the heritagization’s process of Rio de Janeiro (« Rio de Janeiro, carioca landscapes between the mountain and the sea ») at the Unesco as a particular moment when relations between past, present and future are interrogated, in regard of their imbrications with the temporalities of the urban transformations that this city undergoes in the context of « mega-events ». Four moments of this process are analyzed as places of negotiation between the various historicity schemes, created and mobilized by the actors and their imbrications with the times of the urban transformation and those of sustainable development. The purpose is to decipher the imbrications between the temporal horizons of the actors in order to identify the various presents at work in the “make city".